TAFRO Syndrome: A Case Report from Turkey and Review of the Literature - (:unkn) unknown (My University, 2018)
TAFRO syndrome is a rare subtype of the Castleman’s disease which has been described over the last years. The name of TAFRO syndrome comes from thrombocytopenia, anasarca, myelofibrosis, renal dysfunction, and organomegaly. We report a young Turkish male patient presented with fever, night sweats, fatigue, nausea, bilateral pretibial pitting edema, abdominal pain and watery diarrhea. PET/CT revealed multiple lymphadenopathies in cervical, axillary, mediastinal, paraaortic, mesenteric and inguinal lymph nodes. Excisional lymph node biopsy showed atretic germinal centers and expanded interfollicular areas, containing sheets of plasma cells. The R-CHOP regimen was started, and his signs and symptoms improved after the treatment. The current case confirms the unique presentation of this syndrome, helping to understand its clinical course and treatment strategy.
TAFRO Syndrome